Study on the Assessment and Enhancement Path of the Effectiveness of "One Belt, One Road" International Communication Based on Social Media - Wang, Tongle (Transactions on Social Science, Education and Humanities Research, 2024)
Since its inception, "One Belt, One Road" Initiative has become an important platform for promoting global economic cooperation and development. However, in the course of its development, "One Belt, One Road" Initiative has also faced many challenges. In order to effectively deal with these challenges, "One Belt, One Road" Initiative needs to develop a scientific and reasonable communication strategy. As an emerging information dissemination channel, social media has the characteristics of fast dissemination speed, wide coverage and strong interactivity, which provides a new opportunity for the dissemination of "One Belt, One Road" Initiative. Through the use of social media, it is possible to release authoritative information in a timely manner, respond to concerns and questions, display China’s image, and enhance people-to-people communication with countries along the route. At the same time, the data analysis function of social media can be used to understand audience needs and feedback, providing a basis for adjusting and optimizing communication strategies.